Contexts of consumption and their evolution in the digital age: Beyond the service-dominant logic - Roberto Grandinetti; Marco Bettiol; Eleonora Di Maria (Administrative Sciences, 2022)
Starting from the observation of a conceptual gap regarding the association between consumption and the contexts in which it occurs, the paper has two objectives. The first is to fill this gap by developing a framework that includes: the identification of consumption contexts based on their building blocks (actors, goods, relationships), the basic classification of their variety, and a knowledge-based reading of consumption contexts capable of explaining their functioning. The second aim is to show that the framework allows the understanding of the digital transformation of consumption contexts. We show that services are produced in two contexts: in the first type, consumers interact directly with goods; in the second, the intermediation of frontline personnel comes into play. Actors and goods present in the consumption contexts are knowledge-holders, and the relationships between them are learning relationships. The shift from traditional consumption contexts to contexts based on artificial intelligence and the internet of things introduces a major change in that learning relationships are no longer the domain of only (human) actors who learn by interacting with each other and using goods. Both types of contexts are in fact powered by smart goods capable of interacting with each other and with humans within a given context and endowed with structural cognitive connections outside that context.
Keywords: 350; artificial intelligence; consumers; consumption contexts; frontline personnel; goods; services